Sob o signo da curatela : as relações entre família, justiça e medicina em torno dos processos de interdição por diagnósticos de doenças mentais - Barbosa, Luciana Cristina de Campos (2015)
This dissertation aims to analyse the current mechanisms of interdiction of people with “mental illness” diagnosis from the understanding of the relationships between family, justice and psychiatric medicine, built during the legal process. Usually triggered by the family, the interdiction process aims to restrict the civil living acts of a person diagnosed with “mental illness” that characterizes the person as “incapable” from the medical and juridical point of view. With the interdiction sentenced by the judge, a guardian is indicated to be responsible for the goods and the life management of the person that was interdicted, who from this moment on has all his actions considered null for undetermined period. Besides, the interdiction has been used to attest the incapacity of the person to work in cases when the guardian requires a governmental assistance named “Benefício de Prestação Continuada” at the National Institute of Social Security (INSS from the Portuguese abbreviation), on behalf of the interdicted person. The intention, from detailing ethnographic fragments, is to promote the debate on the different meanings of the individual behaviors between the institutions, as well as the relationships between the different knowledges and actions, sometimes conflicting, promoted by this process. The intention is also to embrace moral and ethical questions present in legal, medical, and social speeches about behaviors framed as “symptoms” and “diseases” on the psychiatric knowledge and, because of the medical expertise, disabling from the juridical point of view, as well as its effects in the life of interdicted individuals and their families.